Influence of CurQfen®-curcumin on cognitive impairment: a randomized, double-blinded, placebo-controlled, 3-arm, 3-sequence comparative study - Das, S. Syam; Gopal, Prasad M.; Thomas, Jestin V.; Mohan, Mohind C.; Thomas, Siju C.; Maliakel, Balu P.; Krishnakumar, I. M.; Pulikkaparambil Sasidharan, Baby Chakrapani (Frontiers in Dementia, 2023)
Background: Although curcumin is a blood-brain-barrier permeable molecule with the ability to bind and segregate β-amyloid plaques and neurofibrillary tangles of hyper phosphorylated tau proteins, the poor oral bioavailability, rapid biotransformation to inactive metabolites, fast elimination from systemic circulation and hence the poor cellular uptake has been limiting its clinical efficacy under neurodegenerative conditions.Objective: We hypothesized that the highly bioavailable CurQfen-curcumin (CGM) that has been shown to possess significant blood-brain-barrier permeability and brain bioavailability, would ameliorate dementia under neurodegenerative conditions.In the present double-blinded placebo-controlled 3-arm 3-sequence comparative study, 48 subjects characterized with moderate dementia due to the onset of Alzheimer's disease was randomized into three groups (N = 16/group) and supplemented with 400 mg × 2/day of either placebo (MCC), unformulated standard curcumin complex with 95% purity (USC) or CGM as sachet for six months and compared the relative changes in cognitive and locomotor functions and biochemical markers.Results: Supplementation of CGM produced significant (P < 0.05) improvement in Mini-Mental State Examination (MMSE) and Geriatric Locomotive Function Scale scores (GLFS) in both intra and inter group comparison by 3×2 Repeated Measures ANOVA. Further, analysis of serum levels of biomarkers (BDNF, Aβ42, Tau protein, IL-6 and TNF-α) also revealed a significant (P < 0.05) improvement among CGM subjects as compared to placebo and USC groups.Supplementation CGM as sachet was found to offer significant delay in the progress of Alzheimer's disease as evident from the improvements in locomotive and cognitive functions related to dementia.